Development and Validation of an Instrument for Assessing Patient Experience of Chronic Illness Care - Mira, José Joaquín (Int J Integr Care, 2016)
INTRODUCTION: The experience of chronic patients with the care they receive, fuelled by the focus on patient-centeredness and the increasing evidence on its positive relation with other dimensions of quality, is being acknowledged as a key element in improving the quality of care. There are a dearth of accepted tools and metrics to assess patient experience from the patient’s perspective that have been adapted to the new chronic care context: continued, systemic, with multidisciplinary teams and new technologies. METHODS: Development and validation of a scale conducting a literature review, expert panel, pilot and field studies with 356 chronic primary care patients, to assess content and face validities and reliability. RESULTS: IEXPAC is an 11+1 item scale with adequate metric properties measured by Alpha Chronbach, Goodness of fit index, and satisfactory convergence validity around three factors named: productive interactions, new relational model and person’s self-management. CONCLUSIONS: IEXPAC allows measurement of the patient experience of chronic illness care. Together with other indicators, IEXPAC can determine the quality of care provided according to the Triple Aim framework, facilitating health systems reorientation towards integrated patient-centred care.